Photoluminescence properties of thermally stable highly crystalline CdS nanoparticles (2013)
Thermally stable and highly crystalline CdS nanoparticles were obtained via chemical bath method. The optical properties of CdS nanocrystals were characterized by ultraviolet-vis and photoluminescence spectroscopy. Improvement in the photoluminescence properties of the synthesized CdS nanocrystals was observed. This improvement is believed to be due to highly crystalline CdS nanoparticles which may reduce the local surface-trap states. The CdS nanoparticles were characterized by x-ray powder diffraction (XRD), thermo gravimetric analysis (TGA/DTA) and transmission electron microscopy (TEM).